C1 and C2 vertebrae osteomyelitis: a misleading presentation leading to a fatal outcome - Hassan, Radhiana; J Salmah, Win Mar@ (Faculty of Medicine, International Islamic University Malaysia, 2009)
Cervical vertebral osteomyelitis is rare. While an early and correct diagnosis is critical to prevent catastrophic neurological injury, the diagnosis of cervical vertebral osteomyelitis is often difficult because of its rarity and variable symptoms. We present a case of C1 and C2 vertebrae osteomyelitis with a misleading presentation and its fatal outcome.